The Realization of Direct and Indirect Representative Act by the Panelists of 2019 Atlantic Education Summit - Lestari, Hikmah (Universitas Negeri Semarang, 2021)
This study aims to analyze the realization of direct and indirect representative act by the panelists of 2019 Atlantic Education Summit. This study is designed as spoken discourse study with qualitative approach. The speech act analysis to discourse by Schiffrin (1994) was employed to analyze how utterances are understood and interpreted based on a certain context. The findings are as follows. In terms of frequency, there were 994 direct representative acts and eight indirect representative acts. The high number of direct representative act is related to the effectiveness and efficiency of communication between the panelists and the audiences. In terms of realization, direct representative act is versatile. It means that direct representative act was realized by the panelists to serve so many different purposes of communication, for example assertion, statement, claim, etc. On the contrary, there are several strategies that were employed to realize representative act indirectly. They are associating the certain word with similar object, using words which have non-literal meaning, and using an indirect strategy. In addition, lack of familiarity and the formality of the context are the sources that affect the realization of indirect representative act. Keywords: Representative act, direct, indirect, panelists